Lower hepatic fat is associated with improved insulin secretion in a high-risk prediabetes subphenotype during lifestyle intervention - Wagner, Róbert; Heni, Martin; Kantartzis, Konstantinos; Sandforth, Arvid; Machann, Jürgen; Schick, Fritz; Peter, Andreas; Fritsche, Louise; Szendrödi, Julia; Pfeiffer, Andreas F.H.; Schürmann, Annette; Blüher, Matthias; et al. (Diabetes, 2023)
The objective of this work was to investigate whether impaired insulin secretion can be restored by lifestyle intervention in specific subphenotypes of prediabetes. We assigned 1,045 participants from the Prediabetes Lifestyle Intervention Study (PLIS) to six recently established prediabetes clusters. Insulin secretion was assessed by a C-peptide-based index derived from oral glucose tolerance tests and modeled from three time points during a 1-year intervention. We also analyzed the change of glycemia, insulin sensitivity, and liver fat. All prediabetes high-risk clusters (cluster 3, 5, and 6) had improved glycemic traits during the lifestyle intervention, whereas insulin secretion only increased in clusters 3 and 5 (P < 0.001); however, high liver fat in cluster 5 was associated with a failure to improve insulin secretion (Pinteraction < 0.001). Thus, interventions to reduce liver fat have the potential to improve insulin secretion in a defined subgroup of prediabetes.